VALIDITAS INSTRUMEN TPACK UNTUK GURU MATEMATIKA SEKOLAH MENENGAH PERTAMA - Azkia, Nia; Maarif, Samsul (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This study aims to analyze the validity and reliability of the TPACK (Technological Pedagogical Content Knowledge) instrument for mathematics teacher at the Junior High School (SMP) level in Bekasi Regency. The research method used is a quantitative approach with a cross-sectional survey design, where data were collected through a Likert-based questionnaire consisting of 38 items. The research sample involved 85 mathematics teacher who were randomly selected from public and private schools in Bekasi Regency. Data analysis was carried out using the RASCH model with Winstep 5.1.4.0 software to assess the validity and reliability of the instrument. The results showed that the TPACK instrument met the validity and reliability criteria with person reliability indexes and item reliability showing good consistency. These findings are expected to contribute to the development of a more effective TPACK measurement instrument and can be used as a reference to improve teacher competence in integrating technology into mathematics learning